Electronic thin film reliability - Tu, K. N. (King-ning), 1937- (Cambridge : Cambridge University Press, 2011)
'Thin films are widely used in the electronic device industry. As the trend for miniaturization of electronic devices moves into the nanoscale domain, the reliability of thin films becomes an increasing concern. Building on the author's previous book, Electronic Thin Film Science by Tu, Mayer and Feldman, and based on a graduate course at UCLA given by the author, this new book focuses on reliability science and the processing of thin films. Early chapters address fundamental topics in thin film processes and reliability, including deposition, surface energy and atomic diffusion, before moving onto systematically explain irreversible processes in interconnect and packaging technologies. Describing electromigration, thermomigration and stress migration, with a closing chapter dedicated to failure analysis, the reader will come away with a complete theoretical and practical understanding of electronic thin film reliability. Kept mathematically simple, with real-world examples, this book is ideal for graduate students, researchers and practitioners'--
Includes bibliographical references and index.
Keywords: Thin films -- Textbooks; Reliability (Engineering) -- Textbooks